SOSIALISASI PENTINGNYA MENJAGA KEBERSIHAN LINGKUNGAN: Socialization Of The Importance Of Maintaining A Clean Environment - Aminullah, Aminullah; Apriani, Titin; Titawati, Titin; Sumahiradewi, Luh Gede; Hamid, Hamid; Astuti, Ni Kadek Puji; Nufus, Chairun; Tarmizi, Azhari (Al-Amal: Jurnal Pengabdian Masyarakat, 2025)
The purpose of implementing community service is to socialize the importance of maintaining environmental cleanliness to increase public awareness regarding the impact of an unclean environment and provide an overview of waste management and directly clean the environment. The method for realizing community service activities is "Socialization of the Importance of Maintaining Environmental Cleanliness in Kongok Hamlet, Meninting Village, Batu Layar District, West Lombok Regency" through: 1) Formation of a team or collaboration between lecturers, KKN students and the Meninting village government. 2) Implementation of socialization activities on the beach at the estuary affected by waste, and 3) Environmental cleaning The socialization activity went well and was attended by the Meninting village community, especially the Kongok hamlet. The team consisted of lecturers, KKN students, the Meninting village government and involved youth and the community as participants in the socialization and environmental cleaning. The socialization was said to be successful because the community was directly involved in the agreed cleaning process scheduled once a week. Keeping the environment clean is the obligation of all parties, because the impact of waste will harm all parties, for example, a nest of disease and discomfort to see, or an unpleasant smell, so there needs to be routine cleaning activities and waste processing in every village. Environmental cleanliness also has an impact on the interest and comfort of tourists who visit